Влияние температуры на биологические показатели разных видов и популяций трихограммы - Францевич, Л.А. (Вестник зоологии, 1978)
Parameters characterizing dependence of fecundity and duration of development on temperature were evaluated from original and literature data. They permit calculating the reproduction rate of Trichogramma under cultural and field conditions. The development threshold is near 10°, the sum of effective temperatures above the threshold necessary for development of one generation is 152 days-degs. One may expect reproduction of 4-5 generations per season in the Northern Ukraine and 9-10 generations in the Southern Ukraine. Fecundity directly depends on temperature below the optimum (25°). 1f the fecundity F₂₀ was established at 20° for a certain host, the fecundity at any suboptimal temperature t could be calculated by the formula Fₜ (0.057 t — 0.14)F₂₀. Under equal favourable conditions the fecundity in T. cacoeciae is 30% higher than in T. euproctidis.